Evaluating the sustainable metal packaging for cooked foods among food packaging materials - Balo, Figen; Sua, Lutfu S. (Elsevier, 2023)
This paper provides an investigation of metal packaging materials by a different approach to provide comprehensive evaluation among food packaging. The analytic hierarchy process technique was applied as the analysis methodology. The methodology used in this research combines qualitative and quantitative techniques to find decision alternatives from industry experts, determine the list of evaluation criteria along with their relative importance values, and finally evaluate the packaging materials used for food products. The aim of this study is to help define the best alternative packaging material for cooked foods. Along with the advantages and disadvantages of metal packaging materials, it has been aimed to draw attention to the highlighted characteristics of the packaging materials used for the food products. A list of evaluation criteria is developed along with their relative priorities to evaluate the alternative materials. Subsequently, alternative packaging materials and their performance scores based on this list of factors are calculated. Computational results reveal the most favorable material with the maximum overall score among other options considered in this research. © 2023 Elsevier Inc. All rights reserved.
Keywords: AHP method; Food; Food packing material; MCDM; Metal packaging